Q. 115.0( 1 Vote )

# Equating the coefficients solve the following equations by method of elimination3x – 7y + 10=0y – 2x = 3

As the name holds, method of elimination literally uses elimination technique.

We have,

3x – 7y + 10 = 0

3x – 7y = -10 …(i)

y – 2x = 3 …(ii)

In order to eliminate one of the variables (x and y), we need to make that variable’s coefficient equal in both of the equations.

In this question, it is easy to eliminate y, since both the equations have different signs for variable y. That is, equation (i) has a (-) sign before y and equation (ii) has a (+) sign before y.

Now, we need to make the coefficient of y equal, since in equation (i), y’s coefficient is 7 and in equation (ii), y’s coefficient is 1 (ignoring the signs before it).

For equal coefficient of y, multiply equation (ii) by 7. (Multiplication has to be done over the whole equation as to balance the equation even after making changes)

So, we have from equation (ii),

y – 2x = 3 [× 7

7y – 14x = 21 …(iii)

Now, we have equations (iii) and (i) which can be solved by eliminating variable y.

Recall equation (i) and (iii),

3x – 7y = -10

7y – 14x = 21

Solve these, We get,

-11x = 11 x = -1

Put this values of x in equation (ii), we get

y – 2(-1) = 3

y + 2 = 3

y = 3 – 2

y = 1

Thus, we get our solution as x = -1 and y = 1.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Goprep Genius Quiz on Linear Equations34 mins  Interactive session on Linear Equations in Two VariablesFREE Class  NCERT | Linear Equations41 mins  Quiz | Testing Your Skills on Linear Equation in Two Variables36 mins  Quiz | Important Questions on Linear Equations In Two Variables49 mins  Champ Quiz | Do you Know about Linear Equations ?35 mins  Master Linear Equations40 mins  Quiz | Imp. Qs. on Linear Equations44 mins  Quiz | Solve Problems on Linear Equations37 mins  Champ Quiz | Linear Equation45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 